On stereo processing procedure applied towards blind navigation aid - SVETA - Balakrishnan, G.; Sainarayanan, G.; Nagarajan, Ramachandran; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org